2022
DOI: 10.1002/smll.202201946
|View full text |Cite
|
Sign up to set email alerts
|

A Molten‐Salt Method to Synthesize Ultrahigh‐Nickel Single‐Crystalline LiNi0.92Co0.06Mn0.02O2 with Superior Electrochemical Performance as Cathode Material for Lithium‐Ion Batteries

Abstract: Ni‐rich layered oxides have been intensively considered as promising cathode materials for next‐generation Li‐ion batteries. Nevertheless, the performance degradation caused by intergranular cracks and electrode/electrolyte interface parasitic reactions restricts their further application. Compared with secondary particles, single‐crystal (SC) materials have better mechanical integrity and cycling stability. However, the preparation of ultrahigh‐nickel layered SC cathode still remains a serious challenge. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…46 The unstable lattice O further aggravates the Li/Ni mixing and the contraction of the transition metal slab and Li slab, endangering the layered structure. 47,48 Due to the strong interaction between boron and oxygen (bond enthalpy: 809 kJ mol −1 ), 49 boron in 2#B-LNM can effectively anchor the lattice O, thereby maintaining the coordination number of Ni–O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…46 The unstable lattice O further aggravates the Li/Ni mixing and the contraction of the transition metal slab and Li slab, endangering the layered structure. 47,48 Due to the strong interaction between boron and oxygen (bond enthalpy: 809 kJ mol −1 ), 49 boron in 2#B-LNM can effectively anchor the lattice O, thereby maintaining the coordination number of Ni–O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, by matching the GITT calculation results and cyclic voltammetry (CV) curves, it is found that each phase transition corresponds to a decrease in D Li + , especially in the H2 ↔ H3 phase transition position around 4.2 V. This sharp decline means that the H2 ↔ H3 phase transition is a highly kinetically controlled process, corresponding to the concurrent Li + diffusion and structural rearrangement. 23 Obviously, the CA-NM shows a smoother transition at around 4.2 V compared with the NM, meaning stable kinetic performance. Based on the previous research, 5 it is not only related to the lower Li + /Ni 2+ disorder degree in the initial state, but is also attributed to the fact that Al 3+ preferentially transfers from octahedral interstice sites to the Li layer to hinder the Ni 2+ migration path in a deep charge state.…”
mentioning
confidence: 94%
“…High-temperature and prolonged heating can promote the growth of single-crystal particles to a certain extent, but they cannot easily regulate the orientation of crystal planes and lead to an increase in the degree of particle agglomeration, sodium volatilization, and energy consumption. , The molten salt method is a better choice than the abovementioned method for regulating the size and orientation of single-crystal particles. Although numerous studies have reported the preparation of single-crystal layered oxide cathode materials for LIBs using the molten salt method, only a few studies have been conducted with regard to such materials for SIBs. NaOH and Na 2 SO 4 have been proven to be applicable as molten salts for promoting the growth of Na-based layered oxide single-crystal particles. , Notably, these two molten salts can also encourage the preferential growth of {001} planes (containing planes such as the (002) and (004) planes) while promoting an increase in the size of the single-crystal particles.…”
Section: Introductionmentioning
confidence: 99%